RESEARCH OF LEVELS OF FORMATION OF INDICATORS READYNESS OF FUTURE FOREIGN LANGUAGE TEACHERS FOR PERSONALLY-ORIENTED EDUCATION OF SENIOR STUDENTS - Hladka, O.V. (Pedagogy of Higher and Secondary Education, 2008)
In the article the results of the experimental research of the indices of formation of readiness of future teachers of foreign languages for personality-oriented teaching senior pupils.